The Effect of Photos and a Local-Sounding Name on Discrimination against Ethnic Minorities in Austria - Doris Weichselbaumer; Julia Schuster (Institute of Labor Economics (IZA), 2021)
A large body of research documents the existence of discrimination against migrants and ethnic minorities in the labour market. This study investigates for Austria, to what degree employment discrimination against ethnic minorities is mitigated, when they abstain from following the Austrian norm of including a photograph to their job application that would make their ethnicity salient or when they hold a local sounding name. In our correspondence test, we found that with matching ethnic names and ethnic photographs, black but not Asian job applicants suffered from discrimination. With a local sounding name, blacks (but not Asians) bettered their employment chances. Although photographs may facilitate ethnic discrimination, we did not find that their omission improved minorities' labour market chances. On the contrary, Asians were penalised for leaving out their photograph. Indeed, if candidates did not attach photos despite the convention to do so, we found statistically significant discrimination not only against black, but also Asian applicants.
Keywords: C93; J15; J71; 330; migration; discrimination; hiring; correspondence testing